PENATAAN RUANG DAERAH ALIRAN SUNGAI CILIWUNG DENGAN PENDEKATAN KELEMBAGAAN DALAM PERSPEKTIF PEMANTAPAN PENGELOLAAN USAHATANI (Forum Penelitian Agro Ekonomi, 2021)
Rapid development on Ciliwung watershed converts farmland to other uses causing decreased catchment area and flood. Flood occurrence on Ciliwung watershed indicates that current land use planning is not in accordance with its carrying capacity. Currently, most of the policies issued to manage watershed are dominated by structural approach. Moreover, land use planning often leads regional and sectoral conflicts. Based on a literature study, a non-structural approach should be done prior to a structural approach. Land use planning using an institutional approach is part of a non-structural approach. An institutional approach in managing Ciliwung watershed could be based on Ostrom’s Institutional Analysis and Development (IAD). Payment mechanism for environmental services and compensation can be carried out through the operation and maintenance of irrigation and watershed management simultaneously. Good watershed quality is able prevent flood incidence and to guarantee continuity of irrigation water supply resulting in farming productivity improvement. Optimum allocation of Ciliwung watershed can be achieved by accommodating both conservation and economic requirements simultaneously. Effective institutional interaction is the appropriate way to ensure implementation of integrated watershed management.
Keywords: Ciliwung watershed; land use planning; institutional approach; farming management